STUDY OF POLYMETHACRYLATE (PMA) INFLUENCE AS DISPERSANT ON UBCWM PREPARATION - DATIN F. UMAR; SUGANAL SUGANAL (Puslitbang tekMIRA, 2009)
Upgraded brown coal water mixture (UBCWM) is a mixture of coal resulted from upgraded brown coal (UBC) process with water in a certain ratio to form a homogeneous and stable suspension during storage, transpor- tation and combustion. UBCWM can be used as direct fuel as substitute for heavy fuel oil, particularly in industrial boilers. To obtain a UBCWM with high coal concentration and low apparent viscosity as well as good flow characteristics, the addition of additive as dispersant is needed. To study the effectiveness of polymethacrylate (PMA) as dispersant, research on the effect of PMA in the production of UBCWM needs to be carried out. The research was conducted by preparing UBCWM with the addition of PMA of 0.1, 0.3 and 0.5% and also carboxymethyl cellulose (CMC) of 0.01% as stabilizer. Preparation of UBCWM using 0.3% PMA and CMC, xantham gum (S- 60) and ransham gum (S-194) of 0.01% each was also carried out. Flow characteristic of the UBCWM was measured by using a viscometer at various shear rate. Results indicate that the addition of 0.3% PMA in the production of UBCWM is effective as dispersant. The addition of 0.5% PMA did not significantly reduce apparent viscosity. The addition of 0.3% PMA together with 0.01% CMC produces UBCWM with the highest coal concentration of 58.3% with yield stress of 23.22 Pa.